Female Portrayal in John Green's The Great American Morp and Veronica Roth's Vim and Vigor - Zahran, Fandya Priyandra; Andayani, Ambar (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
The study is designed to be a qualitative descriptive study which aims to analyze and examine the portrayal of female character in John Green’s short story titled The Great American Morp and in Veronica Roth’s Vim and Vigor. The study uses post-feminism theory in conducting analysis on the portrayal of female main character. Identification of character portrayal is conducted by using Murphy’s theory of characterization. The study finds that Green and Roth both portrays their female character under girl power discourse. They normalize that women trait like being lonely, unhappy, introverted, unique, emotional, indecisive, ordinary and being feminine as empowering and acceptable, and not to be taken as weaknesses. Green emphasizes female rebellion toward traditional and popular convention or practices, while Roth encourages an open and positive attitude toward unconventional interpretation in relationship. She highlights the existence of mental health problem of anxiousness in female, specifically in young adult female.